Citizen Seismology in Taiwan: Development, Outreach, and Formative Assessment of Near-Real Time Earthquake Game Competition Activities - Chen, Kate Huihsuan; Liang, Wen-Tzong; Lin, Chun-Hung; Wu, Leon Yufeng (Frontiers in Earth Science, 2020)
Citizen seismology encourages the public involvement in data collection, analysis, and reporting, and has the potential to greatly improve the emergency response to seismic hazard. We believe in the value of citizen seismology and started with distributing Quake-Catcher Network (QCN) sensors at schools in Taiwan. Unlike most of western countries, Earth Sciences is a required course in junior and senior high schools of Taiwan (Ministry of Education, 2014). Low-cost seismometer is potentially a powerful tool in classrooms to teach earthquake science, which makes school teachers our targeted users. We work closely with school teachers and students to understand how can a citizen seismology project can help them to encourage successful engagement. In this study, we establish the achievements gained and problems encountered in different phases of the project since 2013. The main tasks carried out here include (1) refinement of Citizen Seismology Literacy (CSL) into three dimensions: Awareness, and Willingness, and Technology fluency (2) development of an interactive competition platform called the Near-Real Time Earthquake Game Competition (EGCnrt) that allows citizen seismologists to report earthquake information by processing P- and S-wave arrivals, peak ground motion, and first motion of P-waves for every inland M≥4 earthquakes in Taiwan; (3) development of the formative assessment for the 1.5-hour-long, non-lecture-based game activities. Based on 565 student surveys completed after our 2016 summer outreach activity, we found that all three CSL dimensions have an influence on students’ score in the training activity. The final score in EGCnrt is also found to highly correlate with the performance in the three training sections. We therefore, propose that the CSL can act as a powerful indicator for the performance and engagement in earthquake learning activities. The game-based, non-lecture-based learning approach can be effective in promoting citizen seismology in the future.